Clinical Cellular Therapeutics Accelerate Clot Formation - George, Mitchell J.; Prabhakara, Karthik; Toledano‐Furman, Naama E.; Wang, Yao‐Wei; Gill, Brijesh S.; Wade, Charles E.; Olson, Scott D.; Cox, Charles S. (Stem cells translational medicine, 2018)
Clinical cellular therapeutics (CCTs) have shown preliminary efficacy in reducing inflammation after trauma, preserving cardiac function after myocardial infarction, and improving functional recovery after stroke. However, most clinically available cell lines express tissue factor (TF) which stimulates coagulation. We sought to define the degree of procoagulant activity of CCTs as related to TF expression. CCT samples from bone marrow, adipose, amniotic fluid, umbilical cord, multi‐potent adult progenitor cell donors, and bone marrow mononuclear cells were tested. TF expression and phenotype were quantified using flow cytometry. Procoagulant activity of the CCTs was measured in vitro with thromboelastography and calibrated thrombogram. Fluorescence‐activated cell sorting (FACS) separated samples into high‐ and low‐TF expressing populations to isolate the contribution of TF to coagulation. A TF neutralizing antibody was incubated with samples to demonstrate loss of procoagulant function. All CCTs tested expressed procoagulant activity that correlated with expression of tissue factor. Time to clot and thrombin formation decreased with increasing TF expression. High‐TF expressing cells decreased clotting time more than low‐TF expressing cells when isolated from a single donor using FACS. A TF neutralizing antibody restored clotting time to control values in some, but not all, CCT samples. CCTs demonstrate wide variability in procoagulant activity related to TF expression. Time to clot and thrombin formation decreases as TF load increases and this procoagulant effect is neutralized by a TF blocking antibody. Clinical trials using CCTs are in progress and TF expression may emerge as a safety release criterion. Stem Cells Translational Medicine 2018;7:731–739 Clinical cellular therapeutics express different amounts of tissue factor. As their tissue factor load increases, time to clot formation relative to control decreases. Adipose MSCs express high levels of tissue factor and accelerate clot formation the most. Variation in tissue factor load and relative decrease in clotting time are expressed as standard error of the mean.